Determination of Quantitative Macular Perfusion Assessment in Surgical and Non-surgical Cases of Early-stage Myopic Traction Maculopathy - Quiroz-Reyes , Miguel A.; Quiroz-Gonzalez, Erick A.; Quiroz-Gonzalez, Miguel A.; Lima-Gomez, Virgilio (New Horizons in Medicine and Medical Research Vol. 5, 2022)
The present study aimed to compare quantitative changes in macular perfusion in normal eyes, healthy highly myopic eyes, eyes with myopic foveoschisis (MF)/foveoretinal detachment (FRD) not treated surgically, and eyes with early stages of macular traction maculopathy (MTM) and fully resolved myopic FRD treated surgically. This retrospective, consecutive, comparative, interventional, single-surgeon, case-control study was carried out on 118 eyes (104 individuals) between October 2015 and April 2021. Subjects included normal emmetropic eyes (control emmetropia, n = 25); healthy myopic eyes (control high myopia, n = 20); eyes with MF/FRD not treated surgically (non-surgical observational group, n = 28); and structurally fully resolved myopic eyes with FRD treated surgically (surgically treated group, n = 45). Spectral-domain optical coherence tomography (SD-OCT) and OCT angiography were used to assess long-term postoperative structural, functional, and perfusional outcomes. According to the findings, In the surgical group, the mean evolution time of myopic FRD was 6.2 ± 3.6 months. The mean follow-up time was 25.9 ± 10.3 months. The mean time for the myopic FRD resolution was 4.6 ± 1.9 weeks. In the FRD surgical group, median best-corrected visual acuity increased from 0.90 logarithm of the minimum angle of resolution (logMAR; 0.60–1.00) to 0.30 logMAR (0.09–1.00), a highly significant improvement (p < 0.0001). The groups' quantitative vascular density (VD) evaluation results were considerably different (p < 0.001). The superficial foveal avascular zone (FAZ) area was significantly greater in the non-surgical group (p < 0.0001). Lower SD-OCT structural postoperative findings and higher VD quantification values were strongly connected with better final visual acuity results (p < 0.05). The observational group had a considerably higher central subfoveal thickness while the surgical group had a significantly lower central subfoveal thickness (both p<0.05).). Our findings revealed that the surgical group had a higher rate of postoperative microstructural abnormalities on SD-OCT (91.4%) than the non-surgical group, as well as a high rate of statistically significant VD quantitative deficiencies and FAZ abnormalities, and marked improvement in VD and FAZ in the fully surgically resolved myopic FRD group (p < 0.05).